The Relationship Between Family Support for Breastfeeding Companions and Maternal Behavior in Providing Exclusive Breastfeeding - Hidayat, Annisa Nurhayati; Wiwi Wiarsih; Etty Nurkhayati (Papua Medicine and Health Science, 2024)
The achievement of exclusive breastfeeding in Indonesia has not yet reached 80%. In 2013, the exclusive breastfeeding rate was 42%, while in 2015, it was 41%. By 2018, the target had still not been met, with an achievement rate of only 37.3%. One contributing factor is the lack of support from husbands and families. This study aims to determine the relationship between family support for breastfeeding companions and maternal behavior in providing exclusive breastfeeding at Independent Midwife Practice (IMP) Hj. Apipah Rangkasbitung in 2023. This research employs a descriptive-analytic design with a cross-sectional method. The sample consists of 40 mothers with infants aged 6–24 months, selected using a total sampling technique. Data collection was conducted from November to January at IMP Hj. Apipah using a questionnaire. The results show that 55% of mothers received support from their husbands, 55% from their biological mothers, 52.5% from their mothers-in-law, and 70% of mothers provided exclusive breastfeeding. The Chi-Square statistical test indicates a significant relationship between support from husbands, biological mothers, and mothers-in-law in providing exclusive breastfeeding (P-value = 0.000). It is recommended that IMP Hj. Apipah provide Exclusive Breastfeeding Communication, Information, and Education to mothers and families, organize father-focused breastfeeding classes, and establish a family-based breastfeeding support system